The positive impact of survey, question, read, recite, and review (sq3r) strategy on elementary students' reading comprehension - Sulastri, Sulastri; Suhandoko, Astri Dwi Jayanti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The low level of reading comprehension among elementary school students is a major concern in primary education in Indonesia. This study aims to evaluate the positive impact of the Survey, Question, Read, Recite, and Review (SQ3R) strategy on reading comprehension among elementary school students. Through an experimental approach with a one-group pretest-posttest design, students were given a learning intervention using the SQ3R strategy. Data were analyzed using the Wilcoxon test, and the results showed a significance value of 0.000, indicating a significant improvement in text comprehension skills, including identifying main ideas, details, vocabulary, and making inferences after the SQ3R method was implemented. These findings affirm that the SQ3R strategy is not only effective in enhancing comprehensive reading skills but also promotes active student engagement in the learning process. The study suggests the importance of integrating the SQ3R strategy into the elementary school reading curriculum to improve overall student reading comprehension.